Donor-derived cell-free DNA (dd-cfDNA) in kidney transplant recipients with indication biopsy: results of a prospective single-center trial - Benning, Louise; Morath, Christian; Fink, Annette; Rudek, Markus; Speer, Claudius; Kälble, Florian; Nußhag, Christian; Beimler, Jörg; Schwab, Constantin; Waldherr, Rüdiger; Zeier, Martin; Süsal, Caner; et al. (Transplant international, 2023)
Donor-derived cell-free DNA (dd-cfDNA) identifies allograft injury and discriminates active rejection from no rejection. In this prospective study, 106 kidney transplant recipients with 108 clinically indicated biopsies were enrolled at Heidelberg University Hospital between November 2020 and December 2022 to validate the clinical value of dd-cfDNA in a cohort of German patients. dd-cfDNA was quantified at biopsy and correlated to histopathology. Additionally, dd-cfDNA was determined on days 7, 30, and 90 post-biopsy and analyzed for potential use to monitor response to anti-rejection treatment. dd-cfDNA levels were with a median (IQR) % of 2.00 (0.48-3.20) highest in patients with ABMR, followed by 0.92 (0.19-11.25) in patients with TCMR, 0.44 (0.20-1.10) in patients with borderline changes and 0.20 (0.11-0.53) in patients with no signs of rejection. The AUC for dd-cfDNA to discriminate any type of rejection including borderline changes from no rejection was at 0.72 (95% CI 0.62-0.83). In patients receiving anti-rejection treatment, dd-cfDNA levels significantly decreased during the 7-, 30-, and 90-day follow-up compared to levels at the time of biopsy (P=0.006, P=0.002, and P<0.001, respectively). In conclusion, dd-cfDNA significantly discriminates active rejection from no rejection. Decreasing dd-cfDNA following anti-rejection treatment may indicate response to therapy.
Gesehen am 22.03.2024